PROBLEMATIKA DIRI DALAM KARYA LUKIS KONTEMPORER - JEFRIZAL FAHMI, Yasrul Sami, S.Sn., M.Sn., Dra. Lisa Widiarti, M.Sn. (Universitas Negeri Padang, 2017)
The purpose of this final work is to visualize writer condition while solving a problem or fixative problematic in the shape of contemporary paintings, in order to be a lesson and can be interpreted by anyone especially the writer. Embodiment of this work tend to presenting human figure as the main object, also supported by tools and materials that lead to artistic problematic which usually be the elements in every art work. This final work give informations about life problematics is just a simple thing that can be solved with the mindset and also by thingking positively.Key words : art painting, self problematic, contemporary